The Determinants for Creating Valuable Inventions - Karin Beukel (Copenhagen Business School (CBS), 2013)
Empirical studies show that only a small number of all innovations created are valuable innovations. In spite of this, most innovation research focuses on identifying the determinants of innovation, rather than determining the factors influential in generating valuable innovations. The current knowledge therefore can guide organizations to increase innovation output, but not to increase the value of the innovation output. The purpose of this PhD research is to contribute to our understanding of the determinants of valuable innovations by investigating how different intraorganizational factors and uncertainty influence organizations' abilities to generate valuable innovations. This thesis is comprised of four papers, a general introduction and a conclusion. The papers rely on both qualitative and quantitative research methods. One builds on interview data gathered at a Danish university and a firm, one relies on data from the Scandinavian biotech industry, and two papers rely on data from the global hydrocracking industry.
hdl:10398/8828
Keywords: 650